Interaction Study between ESIPT Fluorescent Lipophile-Based Benzazoles and BSA - Thais Kroetz; Pablo Andrei Nogara; Fabiano da Silveira Santos; Lilian Camargo da Luz; Viktor Saraiva Câmara; João Batista Teixeira da Rocha; Alexandre Gonçalves Dal-Bó; Fabiano Severo Rodembusch (Molecules, 2021)
In this study, the interactions of ESIPT fluorescent lipophile-based benzazoles with bovine serum albumin (BSA) were studied and their binding affinity was evaluated. In phosphate-buffered saline (PBS) solution these compounds produce absorption maxima in the UV region and a main fluorescence emission with a large Stokes shift in the blue–green regions due to a proton transfer process in the excited state. The interactions of the benzazoles with BSA were studied using UV-Vis absorption and steady-state fluorescence spectroscopy. The observed spectral quenching of BSA indicates that these compounds could bind to BSA through a strong binding affinity afforded by a static quenching mechanism (Kq~1012 L·mol−1·s−1). The docking simulations indicate that compounds 13 and 16 bind closely to Trp134 in domain I, adopting similar binding poses and interactions. On the other hand, compounds 12, 14, 15, and 17 were bound between domains I and III and did not directly interact with Trp134.